2017
DOI: 10.1038/srep45580
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolomics Reveals Alterations of Electro-acupuncture Stimulations on Chronic Atrophic Gastritis Rats

Abstract: Chronic atrophic gastritis (CAG) is a common gastrointestinal disease which has been considered as precancerous lesions of gastric carcinoma. Previously, electro-acupuncture stimulation has been shown to be effective in ameliorating symptoms of CAG. However the underlying mechanism of this beneficial treatment is yet to be established. In the present study, an integrated histopathological examination along with molecular biological assay, as well as 1H NMR analysis of multiple biological samples (urine, serum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…The rats in control group were freely accessed to water clean water and standard rat diet. According to our previous study 25 , all of rats except ones in control group were subjected to CAG modeling including compulsive sporting, irregular fasting as well as mixture of 30% alcohol and 2% sodium salicylate poured down the throats for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rats in control group were freely accessed to water clean water and standard rat diet. According to our previous study 25 , all of rats except ones in control group were subjected to CAG modeling including compulsive sporting, irregular fasting as well as mixture of 30% alcohol and 2% sodium salicylate poured down the throats for 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…S13 ). According to previous studies 25 , for rats in the electro-acupuncture treatment group, Liangmen (ST 21) and Zusanli (ST 36) were treated with electro-acupuncture (a 30-minute session per day) for 2 weeks after CAG modeling. While for CAG rats with electro-acupuncture on non-acupoints, the corresponding non-acupoints located 5 mm away from each of the two acupoints were treated with electro-acupuncture as mentioned above (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrates that acupuncture may have a potential disadvantage on improving the appetite of depression model rats in comparison with western medicine. Nevertheless, some researches showed that stimulations to acupoints of the stomach meridian such as Sibai (ST 2), Liangmen (ST 21), and Zusanli (ST 36) were effective in treating functional dyspepsia 98 , in which poor appetite is one of the core symptoms. In our analysis, Baihui (GV20) and Yintang (GV29) were most frequently used, while acupoints of stomach are scarcely used.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had proved that the points of the stomach meridian had a good therapeutic effect on gastric mucosal injury [10,16,17]. Meanwhile, our previous studies proved that GU could be treated effectively by acupuncture at Liangmen (ST 21) and Zusanli (ST 36), which belong to the stomach meridian [18][19][20][21]. erefore, "Liangmen" (ST21), "Zusanli" (ST36), "Riyue" (GB24), and "Yanglingquan" (GB34) were selected for treatment by moxibustion (Supplementary Figure S1).…”
Section: Moxibustion Treatmentmentioning
confidence: 99%